Design and pre-clinical evaluation of a universal HIV-1 vaccine. - Sven Létourneau; Eung-Jun Im; Tumelo Mashishi; Choechoe Brereton; Anne Bridgeman; Hongbing Yang; Lucy Dorrell; Tao Dong; Bette Korber; Andrew J McMichael; Tomás Hanke (PLoS ONE)
Background One of the big roadblocks in development of HIV-1/AIDS vaccines is the enormous diversity of HIV-1, which could limit the value of any HIV-1 vaccine candidate currently under test. Methodology and findings To address the HIV-1 variation, we designed a novel T cell immunogen, designated HIV(CONSV), by assembling the 14 most conserved regions of the HIV-1 proteome into one chimaeric protein. Each segment is a consensus sequence from one of the four major HIV-1 clades A, B, C and D, which alternate to ensure equal clade coverage. The gene coding for the HIV(CONSV) protein was inserted into the three most studied vaccine vectors, plasmid DNA, human adenovirus serotype 5 and modified vaccine virus Ankara (MVA), and induced HIV-1-specific T cell responses in mice. We also demonstrated that these conserved regions prime CD8(+) and CD4(+) T cell to highly conserved epitopes in humans and that these epitopes, although usually subdominant, generate memory T cells in patients during natural HIV-1 infection. Significance Therefore, this vaccine approach provides an attractive and testable alternative for overcoming the HIV-1 variability, while focusing T cell responses on regions of the virus that are less likely to mutate and escape. Furthermore, this approach has merit in the simplicity of design and delivery, requiring only a single immunogen to provide extensive coverage of global HIV-1 population diversity.